Implementation of Sharia Compliance in The Halal Tourism Industry In Indonesia (A Study On Sharia Hotels And Beaches) - Mashuri, Ilham (Universitas Islam Indonesia, 2020)
This is a study on the practices of sharia compliance of halal tourism, especially sharia hotels and beaches in Indonesia. This is an empirical juridical research, using qualitative descriptive analytical techniques. The results of this study indicate several points. First, Sharia compliance in the halal tourism industry is a necessity, because sharia compliance is a unique feature of this industry that distinguishes it from the conventional tourism industry and it will maintain the sustainability of this industry because the interests of Muslim consumers are safeguarded and protected. Second, the halal tourism regulatory framework consists of Law Number 40 of 2007; DSN MUI Fatwa Number: 108 / DSN-MUI / X / 2016 concerning Guidelines for Organizing Tourism Based on Sharia Principles; and Minister of Tourism and Creative Economy Regulation No. 2 of 2014 concerning Sharia Business Hotel Operations. However, these regulations are considered inadequate in regulating halal tourism. Third, optimization of sharia compliance in the halal tourism industry is carried out in three steps: first, strengthening the substance by establishing regulations on halal tourism, second, strengthening the structure, and law enforcement officials, and third strengthening the legal culture through socialization and strengthening people's understanding of the importance of sharia compliance in Halal tourism industry.Keywords: halal industry; halal tourism; sharia complianceImplementasi Kepatuhan Syariah Dalam Industri Pariwisata Halal Di Indonesia (Studi Pada Hotel dan Pantai Syariah)AbstrakPenelitian ini merupakan kajian tentang praktik kepatuhan syariah pada pariwisata halal, khususnya hotel dan pantai syariah di Indonesia. Penelitian ini merupakan penelitian yuridis empiris, dengan menggunakan teknik analisis deskriptif kualitatif. Hasil dari penelitian ini menunjukkan beberapa poin: Pertama, kepatuhan syariah dalam industri pariwisata halal merupakan suatu keniscayaan, karena kepatuhan syariah merupakan ciri khas industri ini yang membedakan dengan industri pariwisata konvensional dan akan menjaga keberlangsungan industri ini karena kepentingan konsumen muslim terjaga dan terlindungi. Kedua, kerangka pengaturan pariwisata halal terdiri dari Undang-Undang Nomor 40 Tahun 2007; Fatwa DSN MUI Nomor : 108/DSN-MUI/X/2016 tentang Pedoman Penyelenggaraan Pariwisata Berdasarkan Prinsip Syariah; dan Peraturan Menteri Pariwisata dan Ekonomi Kreatif Nomor 2 Tahun 2014 tentang Penyelenggaraan Hotel Usaha Syariah. Namun, regulasi tersebut dinilai kurang memadai dalam mengatur wisata halal. Ketiga, optimalisasi syariah compliance pada industri wisata halal dilakukan dalam tiga langkah: pertama, penguatan substansi dengan menetapkan regulasi tentang wisata halal, kedua, penguatan struktur, dan aparat penegak hukum, dan ketiga penguatan budaya hukum melalui sosialisasi dan memperkuat pemahaman masyarakat tentang pentingnya kepatuhan syariah dalam industri pariwisata halal.Kata kunci: industri halal; pariwisata halal; kepatuhan syariah